Assessing mathematical communication in elementary fraction learning across different levels of task-specific self-efficac - Siti Muhdiati; Sufyani Prabawanto; Sandi Budi Iriawan; Effy Mulyasari (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: Mathematical communication is a fundamental competency in elementary mathematics because it enables students to represent, explain, and justify mathematical ideas through visual, verbal, and symbolic forms. In fraction learning, these communication processes require students to integrate multiple representations, yet their performance may differ according to task-specific self-efficacy. Aims: This study aimed to assess elementary students’ mathematical communication in fraction learning across different levels of task-specific self-efficacy and to examine the association between self-efficacy and mathematical communication ability. Method: An ex post facto quantitative design was employed involving 176 fifth-grade students from four elementary schools in West Java, Indonesia. Data were collected using a mathematical communication test and a task-specific mathematics self-efficacy questionnaire. Students were classified into low, moderate, and high self-efficacy groups using tertile categorization. Data were analyzed through descriptive statistics, the Kruskal–Wallis test, Bonferroni-adjusted pairwise comparisons, epsilon squared, and Spearman’s rank correlation. Results: Mathematical communication differed significantly across self-efficacy levels (H = 86.635, p < 0.001, ε² = 0.49). Students with higher self-efficacy consistently achieved superior performance across drawing, written explanation, and mathematical expression indicators. Pairwise comparisons confirmed significant differences among all groups, while Spearman’s analysis revealed a strong positive association between self-efficacy and mathematical communication ability (ρ = 0.729, p < 0.001). Conclusion: Task-specific self-efficacy is strongly associated with elementary students’ mathematical communication in fraction learning. Students with higher self-efficacy demonstrated more effective communication across multiple mathematical representations, highlighting the importance of integrating affective factors into mathematics assessment and instruction.